2015
DOI: 10.1111/jace.13861
|View full text |Cite
|
Sign up to set email alerts
|

Electric‐Field‐Driven Phase Transition Process in (K, Na, Li)(Nb, Ta, Sb)O3 Lead‐Free Piezoceramics

Abstract: The electric‐field‐driven phase transition in (K, Na, Li)(Nb, Ta, Sb)O3 lead‐free piezoelectric ceramics was investigated by X‐ray diffraction, Raman spectra, and the temperature dependences of permittivity spectra. After poling under different electric fields, phase of the ceramics transformed gradually from orthorhombic–tetragonal coexisting phase to orthorhombic phase, indicating that the crystal structure of ceramics was strongly sensitive to electric field as an external stimulus. A secondary phase K3Li2N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…With the increase in sintering temperature above 1080°C, the piezoelectric properties weaken, similar to the previous results [18]. According to the experimental data and previous reports, the piezoelectric properties are dependent on the normal ferroelectric characteristics, density and grain uniformity [10]. The more normal ferroelectric characteristics, higher density and more uniform grains can enhance the piezoelectric properties with the increase in sintering temperature up to 1080°C [10].…”
Section: Piezoelectric and Ferroelectric Propertiessupporting
confidence: 89%
See 2 more Smart Citations
“…With the increase in sintering temperature above 1080°C, the piezoelectric properties weaken, similar to the previous results [18]. According to the experimental data and previous reports, the piezoelectric properties are dependent on the normal ferroelectric characteristics, density and grain uniformity [10]. The more normal ferroelectric characteristics, higher density and more uniform grains can enhance the piezoelectric properties with the increase in sintering temperature up to 1080°C [10].…”
Section: Piezoelectric and Ferroelectric Propertiessupporting
confidence: 89%
“…According to the experimental data and previous reports, the piezoelectric properties are dependent on the normal ferroelectric characteristics, density and grain uniformity [10]. The more normal ferroelectric characteristics, higher density and more uniform grains can enhance the piezoelectric properties with the increase in sintering temperature up to 1080°C [10]. The Figure 10 shows the polarization-electric-field (P-E) hysteresis loops of the NKLNTS-ST ceramics (sintered at different temperatures) at room temperature at a frequency of 1 Hz.…”
Section: Piezoelectric and Ferroelectric Propertiesmentioning
confidence: 73%
See 1 more Smart Citation
“…For K 0.5 Na 0.5 NbO 3 -based ceramics, the (200) doublet peak is usually considered to define the structure. For orthorhombic structure, I 002 /I 020 = 2:1 (I = intensity; Feng et al, 2016) but for the tetragonal structure, an opposite trend is observed, having I 002 /I 200 = 1:2 (Zhou et al, 2015). In our samples at x = 0, obvious split of the 200 peak was detected at 2θ ∼ 46 • which is consistent with the orthorhombic phase frequently reported for K 0.5 Na 0.5 NbO 3 ceramics (Sun et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…3 Li et al doped different dopants for the NKN ceramic system, and found that the polymorphic phase boundary (PPB) (the coexistence of the orthorhombic and tetragonal phases) can be obtained at room temperature, which enhances the piezoelectricity piezoelectricity. [4][5][6] Pang et al reported that the density and the piezoelectric properties of NKN-based ceramics can be improved by substituting Li, Ta, and Sb cations into the A and B sites, i.e. (Na 0.52 K 0.4425 )(Nb 0.8925 Sb 0.07 )O 3 -0.0375LiTaO 3 ceramics.…”
mentioning
confidence: 99%